Performance Optimization of Apodized FBG Biomedical Sensor for Variation in Temperature and Presence of Noise. Issue 6 (9th March 2022) - Rani, Saba; Haider, Shafiq; Bukhari, Syed Hashim Raza; Zaidi, Syed Azhar Ali; Huda, Aamina Bintul
Abstract : In this work, comprehensive analysis on single and dual mode, uniform and apodized Fiber Bragg Grating (FBG) based gas concentration measurement sensor performance in the presence of noise and temperature variations is presented. Different scenarios are formulated. Firstly, the indirect sensing method for gas concentration measurement is presented, followed by the discussion on single and dual mode uniform FBG sensor design. Thereafter single and dual mode Gaussian apodized FBG sensor design and its pros and cons are discussed. The effect of temperature variations and noise on FBG sensor is also discussed. Afterwards as per referred literature the simulation results for uniform and apodized FBG in the presence or absence of noise, temperature variations and strain applications are validated. The quantitative analysis shows that the single mode apodized FBG has highest side lobes suppression ratio which is 88.21%. In terms of FWHM single mode apodized FBG has narrowest bandwidth of amplitude 0.18. While dual mode apodized FBG has highest reflectivity, that is, −0.20571. It is observed that reflection spectrum of uniform FBG sensor contains large strength of side lobes at adjacent wavelength. Moreover, the dual mode FBG sensor performance is more affected by variation in temperature and noise but dual mode FBG sensor works better as compared to single mode FBG sensor in context of minimum side lobes, high absorption depth and enhanced reflectivity. The presented investigation will be helpful to prescribe the correct amount of dosage for biomedical application. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.